2016
DOI: 10.1016/j.rppede.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between clinical variables related to asthma in schoolchildren born with very low birth weight with and without bronchopulmonary dysplasia

Abstract: Objective:To assess the prevalence, spirometry findings and risk factors for asthma in schoolchildren who were very low birth weight infants with and without bronchopulmonary dysplasia.Methods:Observational and cross-sectional study. The parents and/or tutors answered the International Study of Asthma and Allergies in Childhood questionnaire. The schoolchildren were submitted to the skin prick test and spirometry assessment.Results:54 schoolchildren who were very low birth weight infants were assessed and 43 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The pathophysiological relationship between esophagus reflux and the worsening of LD in CF is still poorly understood, in comparison with other LD, such as asthma, 18 , 19 , 20 , 21 bronchopulmonary dysplasia, 22 , 23 and chronic obstructive LD in adults. 21 …”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological relationship between esophagus reflux and the worsening of LD in CF is still poorly understood, in comparison with other LD, such as asthma, 18 , 19 , 20 , 21 bronchopulmonary dysplasia, 22 , 23 and chronic obstructive LD in adults. 21 …”
Section: Discussionmentioning
confidence: 99%
“…This long-term damage includes, but is not limited to, persistent pulmonary structure changes (including pulmonary disorder structure, focal atelectasis, focal bronchiectasis and focal emphysema and diffuse pulmonary fibrosis), persistent respiratory dysfunction (forced vital capacity decrease, the first second forced expiratory volume reduction, 25% to 75% reduction in the first percentile forced vital capacity), and almost 25% of children with airway obstruction, while more than 50% have airway hyperreaction, which can lead to severe breathing problems in infancy, childhood and adulthood. These problems include the presence of significant persistent pulmonary dysfunction, recurrent respiratory tract infections, asthma or asthma-like syndrome symptoms, pulmonary hypertension and exercise intolerance [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], which eventually leads to increased readmission rates, and even long-term mortality. In addition to respiratory problems, surviving children with BPD may also have neuropsychiatric problems.…”
Section: Discussionmentioning
confidence: 99%
“…Children born preterm have more respiratory symptoms, including cough and wheezing than controls before adolescence, irrespective of bronchopulmonary dysplasia (BPD), a chronic lung disease that mainly affects extremely preterm infants, which is the most common complication of prematurity, predisposing the infants to the development of obstructive pulmonary diseases [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Several studies showed an increased prevalence of asthma in children with a history of BPD [ 23 , 51 , 52 ], and reduced lung function was less evident in children without BPD than in BPD subjects [ 36 ]. However, it is controversial whether the asthma-like symptoms of children with BPD can be diagnosed as asthma or whether BPD and asthma should be considered different entities having different pathogenetic pathways [ 10 , 53 , 54 ].…”
Section: Airway Impairment and Asthma Developmentmentioning
confidence: 99%